A Linear Programming Model for Long Range Capacity Planning - Fetter, Robert B. (Management Science, 1961)
In comparing long- and short-term commitments to fulfill demand for some kind of capacity, a linear formulation of the problem may prove useful. The general capacity-planning problem treated here is that in which the demand for capacity may be met by ownership, leases of various terms, or spot contracts. Certain kinds of machine capacity, tankers, or trucks might be examples. Variations in demand and prices for the various alternatives give rise to a computational problem of considerable proportions and in addition one must account for the firm's time preference for money. A linear model is presented to aid in developing answers to such questions as the following: (1) What effect will any given demand forecast have on capacity plans, (2) what will be the effect of an expected change in ownership costs, (3) if prices for leased capacity increase by some given amount, how will plans and costs be affected, (4) what is the sensitivity of decisions and costs to forecast error? Computation of an optimal plan under various assumed conditions should provide (1) the best policy for the expected future and (2) those changes in policy which ought to follow from changed conditions.